The efficacy of Levetiracetam compared to Phenytoin in prevention of post-traumatic seizures - Abbas Ali; Ahtesham Khizar; Waseem Ahmed; Pradhumna Kumar Yadav (Romanian Neurosurgery, 2023)
Objectives: To compare the efficacy of Levetiracetam (LEV) versus Phenytoin (PHY) in the prevention of post-traumatic seizures in a low-middle-income country.